2015
DOI: 10.3390/polym7030504
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Mode of Action and Analytical Methods for Evaluation of Gas Phase Activities of Flame Retardants

Abstract: Abstract:The latest techniques used to prove, describe and analyze the gas phase activity of a fire retardant used in polymeric materials are briefly reviewed. Classical techniques, such as thermogravimetric analysis or microscale combustion calorimetry, as well as complex and advanced analytical techniques, such as modified microscale combustion calorimeter (MCC), molecular beam mass spectroscopy and vacuum ultra violet (VUV) photoionization spectroscopy coupled with time of flight MS (TOF-MS), are described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 87 publications
1
76
0
1
Order By: Relevance
“…The three novel compounds were designed in order to possess improved flame retardation potential, but also for a wide range of applications based on their higher melting points and increased stability, which are prerequisites for their use in the production of plastic materials (Buczko et al 2014; Gaan et al 2013, 2015; Neisius et al 2014; Salmeia and Gaan 2015; Salmeia et al 2015; Qiang et al 2011). In contrast to the current practice of investigating the potential harmful properties of flame retardants after their introduction into the market, we applied here a series of human in vitro screening assays to allow a fundamental toxicological classification before the production and application of halogen-free bis -DOPO compounds on an industrial scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three novel compounds were designed in order to possess improved flame retardation potential, but also for a wide range of applications based on their higher melting points and increased stability, which are prerequisites for their use in the production of plastic materials (Buczko et al 2014; Gaan et al 2013, 2015; Neisius et al 2014; Salmeia and Gaan 2015; Salmeia et al 2015; Qiang et al 2011). In contrast to the current practice of investigating the potential harmful properties of flame retardants after their introduction into the market, we applied here a series of human in vitro screening assays to allow a fundamental toxicological classification before the production and application of halogen-free bis -DOPO compounds on an industrial scale.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve its flame retardation potential and influence its physico-chemical parameters, such as its melting point, to allow industrial application in different plastic materials, novel phosphonamidate and phosphonate and phosphinate derivatives of DOPO have been developed (Gaan et al 2009, 2013, 2015; Buczko et al 2014; Neisius et al 2014; Salmeia and Gaan 2015; Salmeia et al 2015), but have not been evaluated with respect to their toxicological potential. In the combustion process, phosphonamidate DOPO derivatives primarily act in the vapor phase by forming phosphorus-containing radical species (PO · ) (Salmeia and Gaan 2015; Salmeia et al 2015), which interact with · OH or H · radicals (Eq. 1) formed during combustion and therefore lead to a reduction in the release of heat, favoring the extinguishing of the flame.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that with increasing concentration of bromine the selfextinguishing time for the foams decreased. 34 When foams are exposed to fire, the volatile component of polymer fuses into the air forming an ignition media leading to initiation step for combustion. While, Ali-1 and Ali-2 showed low flame time of 12.4 and 21 s when the concentration was Br-6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…While, Ali-1 and Ali-2 showed low flame time of 12.4 and 21 s when the concentration was Br-6%, respectively. 18, 34,35 Raman spectroscopy was performed to analyze the graphitic and diamond phase present in the carbon obtained from the burnt specimen of the horizontal burning test. Similar to burning time analysis, area of the burnt specimen is reduced with increasing concentration of bromine.…”
Section: Resultsmentioning
confidence: 99%
“…The fire retardant action is believed to occur in the gas phase (Fenimore and Martin, 1966b, Fenimore and Martin, 1966a, Fenimore and Jones, 1966, Fenimore and Martin, 1972). Yet in spite of the long use and many studies of antimony-bromine systems as fire retardants, for example (Hastie and McBee, 1975, Khalturinskii and Rudakova, 2008, Lewin, 1999, Lewin, 2001, Linteris, 2002, Salmeia et al, 2015, Weil, 2011, Weil and Levchik, 2007), there have been few fundamental studies describing the gas phase inhibition mechanism by antimony and its synergetic effect when combined with chlorine or bromine. Unlike most other gas-phase active flame inhibitors, there are no kinetic or thermodynamic models for antimony flame inhibition, and consequently, there has been no simulation or analysis of those systems.…”
Section: Introductionmentioning
confidence: 99%